O jogo que se sabe jogo: Metaficção e empatia em Undertale - Rodrigues, Matheus Rodrigo Serafim (2024)
This dissertation falls within the field of Communication, focusing on the analysis of the game Undertale, developed independently by Toby Fox and released in 2015. Our research seeks to understand how the game uses a metafictional narrative to create a poetic and rhetorical construct that argues in favor of kindness, peaceful conflict resolution and empathy, arguing that through its internal grammar and relationship with reality, the game is constructed in a way that highlights the very interaction between the player and the game's story. To this end, we initially present a state-of-the-art study, focusing on dissertations and theses from the last five years, using the Brazilian Digital Library of Theses and Dissertations database of the Brazilian Institute of Information in Science and Technology, as well as surveying studies that synergize with this one because they deal with Undertale. Next, we look at the cultural phenomenon surrounding the game and why it is a game changer in the culture of independent games. We also discuss important concepts to define Undertale as an empathy game and metafictional narrative, relying mainly on the work of Jesper Juul (2019), Janet Murray (2017) and Brian Upton (2015) to discuss the relationship between games and digital narratives and Lee & Kim (2020) to define metafiction in games. Finally, we carried out an analysis based on the three-phase model of Petry et al. (2013), focusing on the procedures of studying the context and playing the game itself, seeking to identify when metafictional schemes are applied as a narrative strategy. We then discuss the uses Undertale makes of these moments to tell its story and reinforce its message about empathy and kindness, dividing the analysis into four general classifications of these applications.